Sentinel surveillance of acute respiratory infections and distribution of SARS-CoV-2, influenza A and B, and respiratory syncytial virus in the post-COVID-19 period - Ristić, Mioljub; Patić, Aleksandra; Miljković, Ana; Nikolić, Nataša; Gavanski, Galina; Kovačević, Gordana; Petrović, Vladimir (Vojnosanitetski pregled, 2025)
Background/Aim. Acute respiratory infections (ARIs) remain a major global health concern. The aim of this study was to analyze the epidemiological and clinical characteristics of ARIs and detect the distribution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza A, influenza B, and respiratory syncytial virus (RSV) among outpatients during the 2023/24 and 2024/25 seasons. Methods. A prospective study was conducted through sentinel surveillance, enrolling only patients with ARI symptoms/signs. Identification of one of the four viruses was performed using the CerTest SARS-CoV-2 + Flu A + Flu B + RSV rapid combined test. Results. In the 2023/24 season, 26.57% of samples tested positive for at least one virus, while in the 2024/25 season, a decrease in positivity for the tested viruses was observed, dropping to 14.24%. Influenza A dominated during the 2023/24 season, while the incidence of influenza B increased in early 2025, peaking in late February. SARS-CoV-2 showed moderate fluctuations throughout the study period, with a pronounced peak in September 2024, while RSV remained low during both seasons. The age distribution of patients varied: in the 2023/24 season, RSV and influenza B were most frequently recorded in young children aged 0–4 years, influenza A in children aged 0–4 and 5–14 years, while SARS-CoV-2 was most prevalent among adults aged 30–64 years. In the 2024/25 season, RSV and influenza A were most commonly diagnosed in children aged 0–4 years, influenza B in children aged 5–14 years, and SARS-CoV-2 in individuals over 30 years old. Elevated body temperature was the most common symptom regardless of the type of confirmed viral infection but was significantly less present in SARS-CoV-2 infections compared to other viruses. Conclusion. The results of this study indicate a shift in the dominance of viral causative agents between the observed seasons, with influenza A prevailing in 2023/24, while an increase in the incidence of influenza B virus was observed in 2024/25. SARS-CoV-2 circulated continuously but at a low level, while the impact of RSV was minimal in both seasons.
Keywords: epidemiology; influenza a virus; influenza b virus; respiratory syncytial viruses; respiratory tract infections; sars-cov-2.